2018
DOI: 10.1016/j.trd.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of e-commerce on last-mile light goods vehicle activity in urban areas: The case of London

Abstract: Growth in e-commerce has led to increasing use of light goods vehicles for parcel deliveries in urban areas. This paper provides an insight into the reasons behind this growth and the resulting effort required to meet the exacting delivery services offered by e-retailers which often lead to poor vehicle utilisation in the last-mile operation, as well as the duplication of delivery services in urban centres as competitors vie for business. A case study investigating current parcel delivery operations in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(185 citation statements)
references
References 11 publications
3
152
1
4
Order By: Relevance
“…These analyses, however do not take into account the clear benefit brought by drones in removing vehicles from the road. This could lead to potentially significant reduction of congestion and travel time especially in the most densely populated areas where last-mile delivery associated with eCommerce services has increased the contribution of LCVs to road traffic [43]. Studies commissioned by the European Commission, identify challenges, issues and possible solutions for UFD and logistics [44] including drone operations in residential areas [45].…”
Section: Contextmentioning
confidence: 99%
“…These analyses, however do not take into account the clear benefit brought by drones in removing vehicles from the road. This could lead to potentially significant reduction of congestion and travel time especially in the most densely populated areas where last-mile delivery associated with eCommerce services has increased the contribution of LCVs to road traffic [43]. Studies commissioned by the European Commission, identify challenges, issues and possible solutions for UFD and logistics [44] including drone operations in residential areas [45].…”
Section: Contextmentioning
confidence: 99%
“…Companies whose primary business is providing a service rather than transporting goods mostly use vans [1,22,42]. Service-related trips are increasing with a growing services sector [43].…”
Section: Service-driven Companiesmentioning
confidence: 99%
“…Service-driven companies vary from sole proprietorships to large companies operating a lot of vehicles in an extensive network. The bottom line in both cases is that vehicle-related movement remains largely ignored and is difficult to capture [1,22,42].…”
Section: Service-driven Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…deciding on parking and unloading restrictions), while carriers have a direct interest in where they can stop to make their deliveries as quickly as possible without incurring penalties for illegal parking (UPS incurred $17m in parking fines from their vehicles operating in New York, USA in 2016 [30]). Recent parcel carrier surveys have shown that more than half of their round time can be spent with drivers walking whilst their vehicles are parked by the roadside [1] highlighting the need for suitable places from which to unload and make deliveries. In response to growing pressures on kerbside space, recent developments have included the concepts of 'virtual loading bays', where operators can pay for timeslots to unload on restricted kerb space [43], and 'shared drop zones', where dedicated kerbside staff make 'last 500m' deliveries on behalf of operators [26]; however, both involve added costs for carriers.…”
Section: Related Workmentioning
confidence: 99%